Respuesta :

Answer:

  The solution is (3, -1)

Step-by-step explanation:

Add the two equations together and you get ...

  2d = 6

  d = 3 . . . . . divide by 2

Substitute that value into either equation. For the first, that substitution looks like ...

  3 + e = 2

  e = -1 . . . . . subtract 3

The solution is (d, e) = (3, -1).

_____

Comment on the general solution

As you can see, the larger of the two solutions to this "sum and difference" problem is d=(2+4)/2, the average of the sum and difference. This is generically true for all "sum and difference" problems.